Perancangan Sistem Planned Maintenance dan Man Power Planning di PT X - David Soebiantoro; Siana Halim (Jurnal Titra, 2013)
The purposes of this thesis are designing a planned maintenance and man power planning in the maintenance department of PT X Previously, the PT X used breakdown and corrective maintenance. The maintenance procedures will be revised into corrective maintenance and when continuous production system is executed, corrective & preventive maintenance will be applied. For defining those procedures, first we identified the machines’ failure and redesigned the production system. Additionally, we propose four level of man power planning based on their skill and company management want it divide into four level.